สิทธิมนุษยชนที่ถูกละเมิดโดยรัฐ : ศึกษากรณีการแถลงข่าวผลการจับกุมผู้ต้องหาของข้าราชการตำรวจ - ประมุข ลักษณา (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
In the context of present Thai society, public consciousness as to the relevacne of freedom of thought, freedom of communication, freedom of the press along with the clarity and transparency of the government s acts increases man kindly. Owing to this increase, agerat number of news and information has been released to the public on a constant basis, including those concerning the operations of numerous federal agencies all of which are in the position to impose immense impact on the well-being of the members of the society. Among many others, one of the activity which draws immense public attention is the seizure of criminals by police officers. The Royal Thai police normally issue a press release with a view to prevent any distortion of news and information as well as to ensure their coherence and originality. In the course of this process, however, the suspects are presented to the press regardless of both the mental and social implications of such inconsiderate treatment of them and their impacts that may follow. This kind of act from hence the questions arise; What is the status of the suspects rights? Which acts should be considered a violation of their rights? These questions have been re-investigated on the basis of the concept of human rights in western philosophy. Our studies revealed that the press release of the arrestment issued, of such nature, by the police department is inherently a violation of human rights employing the concepts of human rights of western philosopher. However, out studies on the views of the Thai society on the issue indicated that Thai society does not consider this an act of violation. This is the case of either personnel or public offense. These views of the Thai society emphasize the need for a better understanding of Nature rights, indevidual rights, personal rights and human rights. Only then will the rights of an individual be better protected.